Prevalence of Bolton Discrepancy in Tripoli: Does the Tooth Size Discrepancy Play an Important Role in Malocclusion - Fathi Almadane; Nadia Eddib; Rana Almadane (Khalij-Libya Journal of Dental and Medical Research, 2025)
Discrepancies in tooth size should be known at the initial diagnosis and treatment planning stages if perfect results in orthodontic finishing are to be achieved. A high percentage of finishing phase difficulties arise because of tooth size imbalances. Tooth size discrepancies are considered an important variable, especially in the anterior segment. This study is designed to determine the prevalence of tooth size discrepancy (TSD) in a representative orthodontics population among gender differences and among different class of malocclusion according to angle classifications. As well as to evaluate the ability of simple visual inspection to the upper and lower laterals as well as upper and lower premolars teeth size as suggested by Proffit1 to detect such a discrepancy. the sample Constance of 350 pre-treatment study casts with fully erupted and complete permanent dentitions from first molar to first molar, the random sample was classified into 100 study casts males and 250 study cast females. The sample was classified into 100 case Class I Angle, 150 Case class II Angle and 100 cases was Class III Angle malocclusions. The mesiodistal diameters of the teeth were measured at contact points using digital callipers and the Bolton's analysis was carried out on them. Simple visual estimation of Bolton discrepancy was also performed by Profit’s1 Visual estimation of TSD. As the sample comprised 350 pre-treatment study casts with fully erupted and complete permanent dentitions from first molar to first molar. The males show more anterior ratio Bolton discrepancy 55% than females 46%, 48.5% of the patients had anterior tooth width ratios. Regarding to the different Angle classes of malocclusions, class III malocclusion shows higher overall Bolton ratio TSDs by 65%, followed by class I malocclusion 58% and 48% was in class II malocclusion. In the other hand, the anterior Bolton TSDs ratio was occurred in class III Angle malocclusion by 65 % while class II Angle malocclusion was 47% and class I Angle malocclusion was 33%. Bolton's analysis should be routinely performed in all orthodontic patients and the findings should be included in orthodontic treatment planning. 1.5-2 mm of the required tooth size correction is an appropriate threshold for clinical significance, when aware of possible discrepancies, the orthodontist will be able to anticipate prosthetic work such as composite buildups or mesiodistal reduction when required, sometimes changes in dental inclinations may be used as an orthodontic treatment strategy to resolve anterior Bolton discrepancies and achieve an ideal relationship of incisors. Proffit1 Visual estimation of TSDs was done on the same casts and it was predictable and can be done routinely for each case.